2018
DOI: 10.1038/s41588-018-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for proximal variants improves neoantigen prediction

Abstract: Recent efforts to design personalized cancer immunotherapies use predicted neoantigens, but most neoantigen prediction strategies do not consider proximal (nearby) variants that alter the peptide sequence and may influence neoantigen binding. We evaluated somatic variants from 430 tumors to understand how proximal somatic and germline alterations change the neoantigenic peptide sequence and also impact neoantigen binding predictions. On average, 241 missense somatic variants were analyzed per sample. Of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…NetMHCpan (http://www.cbs.dtu.dk/services/NetMHCpan/) is widely used for peptide prediction (38,(42)(43)(44)(45)(46). Based on previous knowledge, peptide prediction using NetMHCpan showed that the P motif of HLA-A * 30:01-binding peptides was biased toward both A1 supertype-preferred residues (Ile and Leu), and A3 supertype-preferred residues (Arg and Lys) ( Figure 7A).…”
Section: Discussionmentioning
confidence: 99%
“…NetMHCpan (http://www.cbs.dtu.dk/services/NetMHCpan/) is widely used for peptide prediction (38,(42)(43)(44)(45)(46). Based on previous knowledge, peptide prediction using NetMHCpan showed that the P motif of HLA-A * 30:01-binding peptides was biased toward both A1 supertype-preferred residues (Ile and Leu), and A3 supertype-preferred residues (Arg and Lys) ( Figure 7A).…”
Section: Discussionmentioning
confidence: 99%
“…There are several tools to process genomics and transcriptomics data to identify potential neoantigens. These include, for example, PVacTools [80][81][82] and Neopred Pipe [83] These tools can be used to establish mutations likely present in the immunopeptidome, as well as to narrow down those that have affinity for MHC. The best way to integrate the results of these tools, which are of course limited in their ability to predict correctly, with personalized and directly measured immunopeptidomes remains an open question.…”
Section: Detection and Identification Of Immunopeptides With Mass Spementioning
confidence: 99%
“…In addition, pVACseq now makes use of phasing information taking into account variants proximal to somatic variants of interest. Since proximal variants can change the peptide sequence and affect neoantigen binding predictions, this is important for ensuring that the selected neoantigens correctly represent the individual's genome (9). We have also expanded the supported mutation types for neoantigen predictions to include in-frame indels and frameshift mutations.…”
Section: Figure 1: Overview Of Pvactools Workflowmentioning
confidence: 99%
“…The predicted neoantigens are then filtered and ranked based on defined metrics including sequencing read coverage, variant allele fraction (VAF), gene expression, and differential binding compared to the wild type peptide (agretopicity index score (8)). However, of the small number of such prediction tools (Supp Table 1), most lack key functionality, including predicting neoantigens from gene fusions, aiding optimized vaccine design for DNA cassette vaccines, and incorporating nearby germline or somatic alterations into the candidate neoantigens (9). Furthermore, none of the existing tools offer an intuitive graphical user interface for visualizing and efficiently selecting the most promising candidates; a key feature for facilitating involvement of clinicians and other researchers in the process of neoantigen evaluation.…”
mentioning
confidence: 99%